Multifarious Uses of Castor (Ricinus communis L.) - Ramanjaneyulu, A. V.; Anudradha, G.; Ramana, M. Venkata; Reddy, A. Vishnu Vardhan; Gopal, N. Madana (International Journal of Economic Plants, 2017)
Castor (Ricinus communis L.) bean plant has diversified uses as various parts of it can be used in agriculture, industry, medical, and ornamental fields. It is an ideal candidate for production of high value, industrial and oil feed stocks, which was due to high oil (48−52%) and recinoleic acid (85-90%) contents. Its’ unique fatty acid composition allows oil to provide economically competitive feed stocks needed for production of premium quality biodiesel, short chain aviation fuels, fuel lubrication additives and high value biopolymers. Further, various parts of castor plant and oil are used against eye infection, liver disorders and sexually transmitted diseases. Castor cake finds application in Agricultural fields as a nutrient source. Its’ leaf can be used for feeding eri silk worms in ericulture. An attempt was made to document innumerable uses of castor across various sectors as it was not done earlier. The articles discusses future of this crop in the light of increasing demand for ricin free castor besides expanding area and need for enhancing productivity.